Explaining auditors' propensity to issue going‐concern opinions in Australia after the global financial crisis. (15th December 2017) - Carson, Elizabeth; Fargher, Neil; Zhang, Yuyu
Abstract: We document an increase in auditors issuing going‐concern opinions in Australia over a prolonged period since the Global Financial Crisis that is not fully explained by changes in client risk. Overall, our evidence is consistent with auditors reporting more conservatively with the increased level of scrutiny from Australian Securities and Investments Commission inspections and other increased regulation, and in particular, the negative attention following the 2011–2012 inspections. As a result, auditor reports with reference to going‐concern issues have become less informative regarding future corporate failure.